2004
DOI: 10.1055/s-2004-815876
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Case of a Foreign Body Ingestion with Consecutive Small-Bowel Obstruction in a Child

Abstract: A 12-year-old boy with Lennox syndrome presented with an acute abdomen and a history of progressive abdominal pain and vomiting over 3 weeks. The uncommon finding in this case was a foreign body detected in a lower loop of the jejunum causing radiological and clinical signs of jejunitis/ileitis. The foreign body had to be removed surgically and turned out to be a hard (originally soft) plastic part of a towel rack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In contrast, developing countries etiology includes adhesions (34%), hernia (16%), malignancy (13.5%) and tuberculous stricture (10%) [4]. In the pediatric population foreign body ingestion is a known cause of abdominal pain, most of which will pass spontaneously and less than 1% will require surgical removal [5,6]. Acute intestinal obstruction due to foreign bodies is rare in adults [7].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, developing countries etiology includes adhesions (34%), hernia (16%), malignancy (13.5%) and tuberculous stricture (10%) [4]. In the pediatric population foreign body ingestion is a known cause of abdominal pain, most of which will pass spontaneously and less than 1% will require surgical removal [5,6]. Acute intestinal obstruction due to foreign bodies is rare in adults [7].…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel obstruction following ingestion of a plastic part of a towel rack has also been reported in an unusual case. [28] Furthermore, Noel [29] reported a liver abscess developing as a result of FBI. [29] Esophageal hematoma, esophageal stricture, and sacral osteomyelitis are other rare clinical conditions that have occurred due to FBI.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, perforations and mechanical obstruction of the stomach, small bowel, and colon have been reported. [28,36] Goh et al [37] reported that the most frequent perforations were seen in the ileum, at a ratio of 39% in the analysis of 62 cases of FBI causing gastrointestinal perforation, and it was reported that the perforation area was in the distal rectal level in 29% of the patients.…”
Section: Discussionmentioning
confidence: 99%